Polypharmacy, functional outcome and treatment effect of intravenous alteplase for acute ischaemic stroke. (28th October 2020) - Jensen, M.; Boutitie, F.; Cheng, B.; Cho, T.‐H.; Ebinger, M.; Endres, M.; Fiebach, J. B.; Fiehler, J.; Ford, I.; Galinovic, I.; Königsberg, A.; Puig, J.; et al.
Abstract : Background and purpose: Polypharmacy is an important challenge in clinical practice. Our aim was to determine the effect of polypharmacy on functional outcome and treatment effect of alteplase in acute ischaemic stroke. Methods: This was a post hoc analysis of the randomized, placebo‐controlled WAKE‐UP trial of magnetic resonance imaging guided intravenous alteplase in unknown onset stroke. Polypharmacy was defined as an intake of five or more medications at baseline. Comorbidities were assessed by the Charlson Comorbidity Index (CCI). The primary efficacy variable was favourable outcome defined by a score of 0–1 on the modified Rankin Scale at 90 days. Logistic regression analysis was used to test for an association of polypharmacy with functional outcome, and for interaction of polypharmacy and the effect of thrombolysis. Results: Polypharmacy was present in 133/503 (26%) patients. Patients with polypharmacy were older (mean age 70 vs. 64 years; p  < 0.0001) and had a higher score on the National Institutes of Health Stroke Scale at baseline (median 7 vs. 5; p  = 0.0007). A comorbidity load defined by a CCI score ≥ 2 was more frequent in patients with polypharmacy (48% vs. 8%; p  < 0.001). Polypharmacy was associated with lower odds of favourable outcome (adjusted odds ratio 0.50, 95% confidence interval 0.30–0.85; p  = 0.0099), whilst the CCI score was not. Treatment with alteplase was associated with higher odds of favourable outcome in both groups, with no heterogeneity of treatment effect (test for interaction of treatment and polypharmacy, p  = 0.29). Conclusion: In stroke patients, polypharmacy is associated with worse functional outcome after intravenous thrombolysis independent of comorbidities. However, polypharmacy does not interact with the beneficial effect of alteplase. Abstract : In a post hoc analysis of the WAKE‐UP trial, polypharmacy, independently of pre‐existing comorbidities, was associated with worse functional outcome after stroke. Notably, polypharmacy did not modulate the therapeutic effect of intravenous thrombolysis. Based on these results, it is concluded that treatment with alteplase is safe and efficient in patients with polypharmacy, and polypharmacy should not be a reason to exclude these patients from treatment.